Analisis Yuridis Wasiat Wajibah Dalam Kompilasi Hukum Islam - Dwi Dasa Suryantoro Dwi (ASASI: Journal of Islamic Family Law, 2022)
Abstract A binding will is a will whose implementation is not influenced or dependent on the will or will of the deceased testator and does not require evidence that the will was spoken, written or intended, but its implementation is based on a legal basis. must be allowed to do so. Article 209 paragraph (1) and paragraph (2) of the Islamic Law (KHI) regulates wills given to adopted children whose adoptive parents have died or to adoptive parents whose adopted children have died. This is basically an effort to update Islamic law so that it is in line with the legal awareness of the community and fulfills the principles of expediency and justice. The benefit of making a will mandatory for adopted children or adoptive parents is to maintain justice and peace in the family. Even if the adopted child is not a biological child, the obligations of the adoptive parents towards the adopted child are the same as the obligations of the biological child. Therefore, according to the author, the provisions of Article 209 (2) of the KHI are in line with the mashlahah principle which is the "main principle of Islamic law" and therefore in line with Islamic law.